Innovations in Cochlear Implant Technology and their Impact on Pediatric Sensorineural Hearing Loss Rehabilitation - J. A, Khatamov; Xasan o‘g‘li, Lapasov Mirsaid (Journal of Science in Medicine and Life, 2025)
Pediatric sensorineural hearing loss (SNHL) significantly impairs auditory development, language acquisition, and cognitive outcomes. Cochlear implantation (CI) has revolutionized the auditory rehabilitation landscape for children with severe to profound SNHL. Recent innovations in CI technology, including enhanced electrode arrays, wireless connectivity, artificial intelligence integration, and early detection programs, have markedly improved auditory and speech outcomes in pediatric populations. This review explores technological advances, the critical importance of early implantation, and multidisciplinary post-implantation rehabilitation strategies. Clinical outcomes, neuroplasticity considerations, and long-term cognitive benefits are discussed based on contemporary evidence.